Biochemistry and cell culture - Conn, P. Michael; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier/Academic Press, 2012)
Cell biology spans among the widest diversity of methods in the biological sciences. From physical chemistry to microscopy, cells have given up with secrets only when the questions are asked in the right way! This new volume of Methods in Cell Biology covers laboratory methods in cell biology, and includes methods that are among the most important and elucidating in the discipline, such as transfection, cell enrichment and magnetic batch separation. Covers the most important laboratory methods in cell biology Chapters written by experts in their fields.
Includes bibliographical references and index.
Elsevier
Keywords: Cell culture; Cytology -- Technique; SCIENCE -- Life Sciences -- Cell Biology; Cell culture; Cytology -- Technique; Electronic books